2001
DOI: 10.1111/j.8755-8920.2001.450406.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG Anti‐laminin‐1 Autoantibody and Recurrent Miscarriages

Abstract: IgG anti-laminin-1 auto-Abs are associated with recurrent miscarriages and the subsequent pregnancy outcome of recurrent aborters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…Anti-laminin-1 Abs from the immunized mice caused a higher fetal resorption rate with lower embryonic and placental weights (Matalon et al 2003). We have also demonstrated that elevated serum levels of IgG anti-laminin-1 Abs are significantly associated with recurrent firsttrimester miscarriages and infertility with endometriosis (Inagaki et al 2001. These observations suggest that anti-laminin-1 autoAbs may be responsible for reproductive failure, interfering with the early stages of pregnancy.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Anti-laminin-1 Abs from the immunized mice caused a higher fetal resorption rate with lower embryonic and placental weights (Matalon et al 2003). We have also demonstrated that elevated serum levels of IgG anti-laminin-1 Abs are significantly associated with recurrent firsttrimester miscarriages and infertility with endometriosis (Inagaki et al 2001. These observations suggest that anti-laminin-1 autoAbs may be responsible for reproductive failure, interfering with the early stages of pregnancy.…”
Section: Introductionmentioning
confidence: 60%
“…ELISA for anti-laminin-1 antibodies was performed as described by Inagaki et al (2001). Briefly, polystyrene plates (Immulon 1B, Thermo Electron, San Jose, CA) were coated with the purified laminin-1 (10 mg/ml, 50 ml/well) by overnight incubation at 48C.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent clinical study showed that IgG anti-laminin-1 antibodies in blood are significantly associated with the recurrent first-trimester miscarriages in humans (Inagaki et al, 2001). All of these observations suggest that IgG antilaminin-1 antibodies may be responsible for reproductive failure, interfering with an early stage of pregnancy.…”
Section: Clinical Significance Of Igg Anti-laminin-1 Antibodies Recurmentioning
confidence: 99%
“…Solid lines show the mean value. (Inagaki et al, 2001). with the function of laminin-1 to disrupt early reproductive stages and be involved in the development of endometriosis.…”
Section: Infertility Caused By Endometriosismentioning
confidence: 99%